Pengaruh Kadar Timbal (Pb) Terhadap Kerapatan Stomata Dan Kandungan Klorofil Pada Glodokan (Polyalthia Longifolia Sonn) Sebagai Peneduh Kota Di Langsa - Suhaimi Suhaimi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Influence levels of lead (Pb) in plants glodokan (Polyalthia longifolia Sonn) against the density of stomata and chlorophyll was strongly influenced by differences in the number of motor vehicles and physical factors contained in Langsa. The purpose of this study is to determine the factors influencing the accumulation of lead (Pb) in the three streets in the city this Langsa. This research implemented in March 2014, analyzed at the Center for Research and Standard, tissue culture USU (Universitas Sumatera Utara) Medan. The research location is determined by using the method Purpasive Radom Sampling at the third street, namely: Jalan A. Yani, Jalan Sudirman and Jalan Medan B.Aceh. On the road A. Yani biggest influence is a motorcycle with a number of 4384 units, with the accumulation of lead (Pb)